New records of the genus Polysphincta Gravenhorst, 1829 (Hymenoptera: Ichneumonidae: Pimplinae) from the Oriental region - Varga, Oleksandr; Reshchikov, Alexey (Zootaxa, 2015)
A new species, Polysphincta punctigaster Varga & Reshchikov sp. n., the second known species of the genus from the Oriental region, is described from Thailand. Polysphincta asiatica Kusigemati, 1984 is considered to be a junior synonym of P. boops Tschek, 1869 (syn. nov.). Polysphincta longa Kasparyan, 1976 is recorded from the Oriental region for the first time.